CHARACTER BUILDING UNTUK MENIGKATKAN KESEJAHTERAAN PSIKOLOGIS PADA ANAK PANTI ASUHAN DI KECAMATAN SEKUPANG KOTA BATAM - Cevy Amelia; Yuditia; Dhea Amelya Saputri; Novita Sari (LPPM-Universitas Batam, 2024)
The implementation of this community service is to improve children's ability to understand the meaning of their potential which is then applied to their future orientation. This is very good if introduced from an early age, namely children who are already at school and already have optimal creative imagination. This activity supports children's ability to express his aspirations for the future. If trained, it will form character formation that improves psychological well-being in children.